Vortices in a mesoscopic superconducting circular sector - Sardella, Edson [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Malvezzi, André Luiz [UNESP] (American Physical Society (APS), 2008)
In the present paper we develop an algorithm to solve the time dependent Ginzburg-Landau equations, by using the link variables technique, for circular geometries. In addition, we evaluate the Helmholtz and Gibbs free energy, the magnetization, and the number of vortices. This algorithm is applied to a circular sector. We evaluate the superconduting-normal magnetic field transition, the magnetization, and the superconducting density. Our results point out that, as we reduce the superconducting area, the nucleation field increases. Nevertheless, as the angular width of the circular sector goes to small values the asymptotic behavior is independent of the sample area. We also show that the value of the first nucleation field is approximately the same independently of the form of the circular sector. Furthermore, we study the nucleation of giant and multivortex states for the different shapes of the present geometry. © 2008 The American Physical Society.